Rekontruksi Penguatan Pesantren dalam Pengembangan Civil Society di Era Globalisasi - Abdul Ghofur (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2016)
The role of pesantren in the development of civil society in this era of globalization needs to be re-examined. Along with the various challenges in this era, certain steps required to reconstruct the strengthening of the role of pesantren. Pesantren which has been able to play a role of educating the students should be developed with greater emphasis on strengthening civil society more comprehensively. Based on data and analysis, the authors conclude that: First, schools in addition to religious education institutions, also has the potential for the development of civil society in public education by taking various measures. Second, the schools in conducting educational development of civil society in the community can take two ways: (1) perform variety useful and beneficial activities to the surrounding community (2) to make educational planning directed at the ability and skills of the students respond to the needs and demands communities of origin. Third, the main role of schools in developing Islamic religious education should continue to be empowered and developed primarily related to entrepreneurship and independence, as well as efforts to integrate the religious knowledge and development of civilization in this era of globalization. Peran pesantren dalam pengembangan civil society di era globalisasi ini perlu untuk dikaji ulang. Seiring dengan adanya berbagai tantangan di era ini, langkah-langkah tertentu diperlukan untuk merekontruksi penguatan peran pesantren ini. Pesantren yang selama ini mampu berperan mendidik para santri hendaknya dikembangkan dengan lebih menekankan pada penguatan civil society secara lebih komprehensif. Berdasarkan  data dan analisis,  penulis menyimpulkan bahwa: Pertama, pesantren di samping sebagai lembaga pendidikan agama, juga memiliki potensi untuk melakukan pengembangan pendidikan civil society di masyarakat dengan melakukan berbagai upaya. Kedua, pesantren dalam melakukan pengembangan pendidikan civil society di masyarakat dapat menempuh dua cara: (1) melakukan berbagai akvititas yang berguna dan bermanfaat bagi masyarakat di sekitarnya (2) dengan membuat perencanaan pendidikan yang diarahkan pada kemampuan dan ketrampilan para santri dalam merespon kebutuhan dan tuntutan masyarakat asalnya. Ketiga, peran utama pesantren dalam melakukan pengembangan pendidikan agama Islam hendaknya terus diberdayakan dan dikembangkan terutama terkait enterpreneurship dan kemandirian, serta upaya memadukan antara pengetahuan agama dan kemajuan zaman di era globalisasi ini.